Effects of Product Quality and Price on the Purchase Decision in Shopee Marketplace (A Case Study at Department of Business Administration, Politeknik Negeri Medan) - Rahmadani Koto; Ocdy Amelia; Cahyo Pramono (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Business world in the digital era is developing rapidly today which causes business development increasingly to lead to intense competition. Technological advances make it possible to carry out business relationships through a technological device known as internet. This business activity that utilizes the internet is known as a marketplace. The research entitled "Effects of Product Quality and Price on the Purchase Decision in the Shopee Marketplace" is the result of a quantitative research aiming at answering the questions about the effects of product quality and price on the purchase decision in Shopee Marketplace. The research employs quantitative research method. The samples are taken by using simple random sampling technique. The data are collected by distributing questionnaires and analyzed by using multiple linear regression analysis. Based on the results of the partial test statistical calculations, it is concluded that, partially, product quality has some effects on the purchase decision in Shopee Marketplace. It is proved that product quality and price, offered by Shopee marketplace meet the consumers’ expectation, and, especially the very reasonable price compared with the other marketplaces as their competitors.